El viaje del alma al más allá. Un paralelo entre Hititas y Órficos - Bernabé, Alberto (Revista de Filología Románica, 2006)
The paper compares two tales that describe a journey of the human soul to the underworld: one of them was included in a Hittite ritual called «The Voyage of the Immortal Human Soul» and the other that was told in the Greek texts written in the Orphic gold leaves. Both tales consider the passage of the soul into the otherworld as a travel to the underground and tell that there are two different places in the otherworld: a grateful field and a negative one characterized by mud and oblivion. In both stories the death of a goddess’ son is recalled. But they have also great differences, due to the different religious background in each of them